Bolton ratio in subjects with normal occlusion and malocclusion - Ivan Delgado Ricci; Marco Antonio Scanavini; Armando Koichiro Kaieda; Henrique Damian Rosário; Luiz Renato Paranhos (Universidade Estadual de Campinas, 2015)
Aim: To verify the presence of Bolton anterior and total discrepancy in Brazilian individuals with natural normal occlusion and Angle's Class I and Class II, division 1 malocclusions. Methods: The sample was divided in three groups (n=35 each): natural normal occlusion; Class I malocclusion; Class II, division 1 malocclusion. Of the 105 Caucasian Brazilian individuals, 24 were boys and 81 were girls aged from 13 to 17 years and 4 months. The mesiodistal width of the maxillary and mandibular teeth, from the left first molar to the right first molar, was measured on each pre-treatment dental plaster cast using a digital caliper accurate to 0.01 mm resolution. Values were tabulated and the Bolton ratio was applied. The Kolmogorov-Smirnov test was used to verify if data were normally distributed (p>0.2). For comparison between the values obtained and those from the Bolton standard, Student's t test was used and one-way ANOVA was used for comparisons among the 3 groups, with a significance level of 5% (p<0.05). Results: For groups 1, 2 and 3, respectively, the total ratio found was 90.36% (SD 1.70), 91.17% (SD±2.58) and 90.76% (SD±2.45); and the anterior ratio was 77.73% (SD 2.39), 78.01% (SD 2.66) and 77.30% (SD 2.65). Conclusions: There was no significant difference among the groups regarding the values indicated in the Bolton ratio.